The power of translation: Innovation dialogues in the context of farmer-led innovation in the Algerian Sahara. (April 2020) - Naouri, Mohamed; Kuper, Marcel; Hartani, Tarik
Abstract: Developing irrigation technology for a diversity of farmers with rapidly changing demands can be hard for designers, especially when the technology concerns smallholders in developing countries. Innovation networks supporting the adopted technology increasingly include both globalised players and very local actors, making innovation intermediaries capable of translating innovation issues for different actors increasingly indispensable. The aim of this study was to analyse the two-way process of technology translation between international manufacturers and smallholders and to characterise the power struggle between different actors in a farmer-led drip irrigation innovation process. The study was carried out in Biskra, a growing production basin for early greenhouse vegetables in the Algerian Sahara. We conducted 42 interviews with farmers and 42 interviews with other actors involved in the innovation process. First, we show how farmers took over the drip irrigation translation by adapting the technology to local conditions and by creating an innovation network to support the production, diffusion and use of the technology. Second, we identified the different innovation intermediaries involved in the dialogue surrounding drip irrigation, who play an active and crucial role in the multi-scale, multi-actor process of translating agricultural technology, in addition to supplying farm inputs to farmers. International manufacturers use these intermediaries, but also target direct dialogue with farmers to anticipate the future directions of agricultural systems and to remain competitive. Third, we show that to survive, technology translation requires active but stable channels for two-way dialogue between manufacturers and farmers. Fourth, we show that innovation networks are not conflict free, as there is a continuous struggle for power and influence among the different actors. The key element in this power struggle is controlling the technology translation process. The better you control the translation, the more powerful you are in the innovation system. Highlights: Farmer-led innovation of drip irrigation enabled adapting it to local conditions. Adapting drip irrigation technology led to reorganise the innovation network. Technology translation requires active, stable dialogue channels. Innovation intermediaries play an active role in translation. Translation is key for gaining power in innovation networks.